AN ANALYSIS OF TEACHER AND STUDENT TALK IN THE CLASSROOM INTERACTION OF THE EIGHTH GRADE OF SMP NEGERI 18 PURWOREJO - Semi Sukarni; Siti Ulfah (Vision: Journal for Language and Foreign Language Learning, 2015)
The aims of this research are fi rstly, to describe the interactionused by the teacher and studentsconducted in the classroomof theeighth grade of SMP Negeri 18 Purworejo in the Academic Year2012/2013; secondly, to know what type of interaction characteris-tics of the teacher-student talk in the classroom interaction; thirdly,to identify languages used in the classroom interaction used duringteaching-learning process.This thesis is a descriptive qualitative study on teacher and stu-dent talk in the classroom interaction, particularly on the partici-pants’ interaction in SMP N 18 Purworejo. The data of this studyare the interaction between the teacher and the students in the class-room. In order to analyze the data, some steps are conducted. Thedata was taken by recording the classroom interaction. The subjectin this research wasthe grade VIIIG of SMP Negeri 18 Purworejo,there were 40 students and one English teacher. The researcher usedobservation and recording for collecting the data. Flanders’ Interac-tion Analysis was used to identify and analyze teacher-student talkin the classroom interaction.The result of this study shows that the teacher was more ac-tive in the interaction. Meanwhile, the student was less active than the teacher. Based on the fi nding, the researcher concludes that theteacher was dominant in the classroom interaction. The percentageof the teacher talk was 78.15%,whereas the students’ participationwas 21.16%.the studentsnot balance between Indonesianand English. Indonesian is 62% while English is only 38%. Itshows that teacher used more Indonesian than English when sheexplains the material. The interaction was in three ways communi-cation: interaction between teacher-students, students-teacher, andstudents-students.